2016
DOI: 10.1017/s1047951116000160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic treprostinil treatment on experimental right heart hypertrophy and failure

Abstract: In the pulmonary trunk banding model of pressure overload-induced right ventricular hypertrophy and failure, moderate- and high-dose treatment with treprostinil did not improve right ventricular function neither in compensated nor in decompensated right heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
(60 reference statements)
1
10
0
Order By: Relevance
“…We tested the effects of low‐dose (100 ng·kg −1 ·min −1 ; Trep‐100) and high‐dose (810 ng·kg −1 ·min −1 ; Trep‐810) treprostinil on established PAH using the rat SUHx model of severe PAH. The low and high doses of treprostinil were selected based on the previous studies that investigated the effects of treprostinil in pulmonary artery banding model and that demonstrated reversal of established PAH in MCT model (Yang et al ., ; Zhou et al ., ; Axelgaard et al ., ). To confirm a clinically relevant plasma concentration of treprostinil was achieved in our study, we analysed the plasma levels of treprostinil in naïve, vehicle, Trep‐100 and Trep‐810‐treated rats.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We tested the effects of low‐dose (100 ng·kg −1 ·min −1 ; Trep‐100) and high‐dose (810 ng·kg −1 ·min −1 ; Trep‐810) treprostinil on established PAH using the rat SUHx model of severe PAH. The low and high doses of treprostinil were selected based on the previous studies that investigated the effects of treprostinil in pulmonary artery banding model and that demonstrated reversal of established PAH in MCT model (Yang et al ., ; Zhou et al ., ; Axelgaard et al ., ). To confirm a clinically relevant plasma concentration of treprostinil was achieved in our study, we analysed the plasma levels of treprostinil in naïve, vehicle, Trep‐100 and Trep‐810‐treated rats.…”
Section: Resultsmentioning
confidence: 99%
“…Axelgaard et al . has also demonstrated that the chronic treatment with treprostinil in a moderate or high dose does not reverse or attenuate RV hypertrophy or function in pulmonary artery banding model (Axelgaard et al ., ) that is contrary to the effects of iloprost (Holmboe et al ., ). Further, the lack of direct inotropic effect of PGs on isolated atrial strips from the normal and pressure‐overloaded human right hearts has been reported (Holmboe et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…PT banding was performed with a clip compressed to an inner diameter of 0.6 mm as described previously. 4 , 8 Three days before PT banding surgery, the rats were randomized to treatment with levosimendan 3 mg/kg/day (Orion Pharma, Espoo, Finland) (n = 13 out of 29) or vehicle (n = 16 out of 29) added to the drinking water. Control rats without PT banding received vehicle treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Echocardiography was performed before PET scanning as described elsewhere. 4 , 8 On the day of PET scanning, 20 of the 40 rats were submitted to 11 C-acetate PET to determine the effect of levosimendan on RV MEE, and 20 of the 40 rats were submitted to 18 F-FDG PET to investigate potential levosimendan-induced changes in RV metabolism ( Fig. 1b and 1c ).…”
Section: Methodsmentioning
confidence: 99%